Flexible humidity photoluminescent fiber as well as preparation method and application thereof
By hydrothermal growth of small rare earth metal organic frame particles on the surface of flexible high-temperature resistant fibers, the problems of limited fiber performance and unresistance to high temperature in the prior art are solved, and the preparation of humidity-sensitive photoluminescent fibers is realized, with excellent flexibility and Luminous performance.
Patent Information
- Application Number
- CN202411412552.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2044-10-11
AI Technical Summary
In the prior art, the preparation method of photoluminescent fibers requires the imparting of active groups to the fiber membrane through surface chemical modification technology, resulting in limited fiber performance and the fibers not resistant to high temperatures, limiting the preparation conditions.
Flexible high-temperature resistant fibers are used as substrates, and small particles of regular rare earth metal organic frames are grown on their surfaces by hydrothermal method to form humidity-sensitive photoluminescent fibers.
The fiber surface is stable and uniformly deposited fluorescent material particles, overcoming the technical bias that the fiber-formed substrate cannot stabilize the fluorescent material loading, and the fiber has good flexibility, luminous performance and stability.
Smart Images

Figure CN119491416A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of photoluminescent fiber preparation, and in particular to a flexible humidity photoluminescent fiber and a preparation method and application thereof. Background Art
[0002] Photoluminescence refers to the phenomenon that an object relies on external light sources to obtain energy, which leads to excitation and luminescence. It generally goes through three main stages: absorption, energy transfer and light emission. The absorption and emission of light both occur in transitions between energy levels and go through excited states. Energy transfer is due to the movement of excited states. Ultraviolet radiation, visible light and infrared radiation can all cause photoluminescence, such as phosphorescence and fluorescence.
[0003] Assembling water vapor-sensitive fluorescent molecules with polymer networks to obtain sensing materials is considered to be an effective method for achieving visual humidity detection. Fluorescence sensing does not require external microelectronic devices. Through the changes in the polarity of the microenvironment induced by external water vapor on the fluorescent material, different "naked eye" visible colors are obtained by UV light excitation, thereby realizing the sensing of the humidity of the external environment. The combination of humidity photoluminescence and fiber has greatly expanded the application prospects of photoluminescence. As a new type of functional material, humidity photoluminescent fiber has a wide range of uses in sensing, bionics, clothing, and medical treatment.
[0004] The invention patent with publication number CN107747222A provides a fluorescent organic framework based on electrospinning technology and its preparation method. The method first prepares amino-rich chitosan / polyethylene oxide nanofiber membrane as a base nanofiber membrane by electrospinning, then immerses the base nanofiber membrane in a carboxyl-rich activation solution, and the amino groups of the base nanofiber membrane link the carboxyl groups of trimesic acid in the activation solution to obtain a carboxyl-rich fiber membrane sample, and finally, hydrates fluorescent metal nitrate and trimesic acid are dissolved in ethanol and water to form a solution, and the carboxyl-rich fiber membrane sample is immersed in the solution, and the solution is placed in a closed container, and triethylamine is injected into the container and allowed to volatilize naturally, and the fluorescent metal ions and trimesic acid ligands begin to assemble on the carboxyl-rich fiber surface and grow into a uniform fluorescent MOFs crystal / chitosan composite membrane. However, this preparation method requires the use of surface chemical modification technology to give the fiber membrane surface numerous active groups in order to achieve mutual loading between the fiber membrane and the fluorescent material, which will lead to certain limitations and influences on the performance of the fiber membrane itself. In addition, since the fiber membrane is not resistant to high temperatures, there is a technical defect that the reaction conditions are limited and it can only be prepared under low temperature conditions.
[0005] In view of this, it is necessary to study a flexible humidity photoluminescent fiber and its preparation method and application to solve the above technical problems. Summary of the invention
[0006] In view of the technical problems existing in the background technology, the present application provides a flexible humidity photoluminescent fiber and its preparation method and application, using a flexible high temperature resistant fiber as a substrate, hydrothermally growing regular rare earth metal organic framework small particles on its surface, and obtaining a flexible humidity photoluminescent fiber. When the fiber material is wet, it can emit bright blue light under ultraviolet light, that is, the humidity photoluminescent fiber is obtained. The humidity photoluminescent fiber prepared by the present invention has good flexibility, excellent luminescent performance and stability, and has good application prospects in the field of smart wearables and visualized smart fibers.
[0007] In a first aspect, the present invention provides a method for preparing a flexible humidity-induced photoluminescent fiber, comprising the following steps:
[0008] S1, first, using N,N-dimethylformamide as a solvent to prepare a 2-aminoterephthalic acid solution; then, adding a rare earth metal organic framework precursor to obtain a precursor mixed solution;
[0009] S2, performing ultrasonic treatment on the precursor mixed solution;
[0010] S3, placing the pretreated high temperature resistant fiber in the ultrasonically treated precursor mixed solution for hydrothermal reaction, wherein the hydrothermal temperature is 120 to 180° C. and the reaction time is 24 to 72 hours;
[0011] S4, after the hydrothermal reaction is completed and the solution is cooled to room temperature, the high temperature resistant fiber is taken out and cleaned and dried, and humidity-sensitive photoluminescent organic metal framework particles with a predetermined thickness, predetermined particle size and crystal form are uniformly deposited on the surface of the flexible high temperature resistant fiber to obtain a flexible humidity photoluminescent fiber.
[0012] As a further improvement of the present invention, in the precursor mixed solution in step S1, the concentration of the rare earth metal organic framework precursor is 0.02-0.06 mol / L; the concentration of the 2-aminoterephthalic acid solution is 0.01-0.03 mol / L.
[0013] As a further improvement of the present invention, in the precursor mixed solution in step S1, the molar mass ratio of the rare earth metal organic framework precursor to 2-aminoterephthalic acid is 2.2:1.1 (2:1).
[0014] As a further improvement of the present invention, the rare earth metal organic framework precursor is a mixture of one or more of neodymium nitrate hexahydrate, europium nitrate hexahydrate, terbium nitrate hexahydrate, and terbium nitrate hexahydrate.
[0015] As a further improvement of the present invention, in step S3, the high temperature resistant fiber is one of carbon fiber, metal-based fiber, polyester fiber, polytetrafluoroethylene fiber, and polyimide fiber.
[0016] As a further improvement of the present invention, in step S3, the specific process of the hydrothermal reaction is: placing the precursor mixed solution in a hydrothermal reactor, and then putting in the pretreated high-temperature resistant fiber, wherein the hydrothermal temperature is 120-150°C, and the reaction time is 24-48h.
[0017] As a further improvement of the present invention, in step S2, the process of ultrasonic treatment is as follows: placing the precursor mixed solution in an ice bath at 0-10°C, the ultrasonic time is 10-30 minutes, and the ultrasonic power is 200-500W.
[0018] As a further improvement of the present invention, in step S3, the pretreatment process of the high temperature resistant fiber is: placing the high temperature resistant fiber in water and alcohol solution in turn for ultrasonic cleaning, and then taking it out and drying it for standby use.
[0019] As a further improvement of the present invention, in step S3, the particle size of the humidity-sensitive photoluminescent organic metal framework particles is 1 to 2 μm, the crystal form is monoclinic, and the deposition thickness is 2 to 4 μm.
[0020] In a second aspect, an embodiment of the present application provides a flexible humidity-induced photoluminescent fiber, which is prepared by the above-mentioned method for preparing a flexible humidity-induced photoluminescent fiber;
[0021] The flexible humidity photoluminescent fiber includes a high temperature resistant fiber matrix and humidity sensitive photoluminescent organic metal framework particles uniformly deposited and loaded on the surface of the high temperature resistant fiber; the humidity sensitive photoluminescent organic metal framework particles have a particle size of 0.5 to 2.5 μm, a monoclinic crystal system, and a deposition thickness of 1 to 4 μm. ;
[0022] The flexible humidity photoluminescent fiber is stimulated by the change of environmental humidity and emits blue fluorescence under the irradiation of ultraviolet light.
[0023] In a third aspect, the embodiments of the present application provide applications of the flexible humidity-induced photoluminescent fiber described above in the fields of smart wearables, smart anti-counterfeiting, and environmental monitoring.
[0024] The beneficial effects of the present invention are:
[0025] 1. The preparation method of the flexible humidity photoluminescent fiber provided by the present invention comprises the following steps: firstly, the surface of the high temperature resistant fiber is pretreated to make the fiber surface smooth and clean; the treated high temperature resistant fiber is placed in a mixed solution system containing neodymium nitrate hexahydrate (rare earth metal organic framework precursor), 2-aminoterephthalic acid and N,N-dimethylformamide, and the high temperature resistant fiber is chemically treated by a hydrothermal method. The high temperature hydrothermal reaction causes organic metal framework particles to grow and deposit on the fiber surface to form a dense photoluminescent layer, thereby obtaining the humidity photoluminescent fiber; the flexible humidity photoluminescent fiber has good flexibility, excellent color change performance and stability. In this mixed solution system, the following reaction process can occur when neodymium nitrate hexahydrate, 2-aminoterephthalic acid and N,N-dimethylformamide are mixed: first, a thin linear MOF is hydrothermally grown to form a dense film on the fiber surface, which is further composed of spherical MOF particles. This allows the present invention to directly achieve stable and uniform deposition and loading of fluorescent organic metal framework particles on the smooth fiber surface, overcoming the technical prejudice in the prior art that fiber-shaped substrates cannot stably, firmly and uniformly deposit and load fluorescent material particles.
[0026] 2. The preparation method of the flexible humidity photoluminescent fiber provided by the present invention can effectively regulate the deposition thickness, particle size and crystal form of the organic framework metal particles deposited on the surface of the high temperature resistant fiber by regulating the molar ratio of the precursor dosage and the hydrothermal reaction parameters, so that the organic framework metal particles are tightly and firmly combined with the fiber substrate, while significantly enhancing the luminescence performance of the fiber, thereby effectively regulating the luminescence brightness and stability of the flexible high temperature resistant fiber, so that the obtained flexible humidity photoluminescent fiber has good flexibility, fast response time, excellent stability and luminescence brightness, and has good application prospects in the field of smart wearables and visualized smart fibers.
[0027] 3. The preparation method of the flexible humidity-sensitive photoluminescent fiber provided by the present invention can further effectively regulate the mechanical properties of the fiber while realizing the function of humidity-sensitive photoluminescence by regulating the deposition thickness, particle size and crystal form of the organic metal framework particles, that is, it can significantly enhance the tensile properties and flexibility of the fiber at the same time. The present invention associates the flexibility of the fiber with the characteristics of the organic metal framework particles to achieve a synergistic effect.
[0028] 4. The flexible humidity photoluminescent fiber provided by the present invention can emit blue fluorescence of different intensities under the irradiation of ultraviolet lamp as the humidity changes. The luminous effect is obvious, the luminous time when wet is fast and the stability is good. When the humidity reaches 100%, under the irradiation of ultraviolet lamp, the fiber emits extremely bright blue light. It has good application prospects in the field of smart wearables and visualized smart fibers, and has huge commercial promotion value.
[0029] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the technical solution of the present application, the following is a brief introduction to the drawings used in the present application. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0031] Figure 1 This is a scanning electron microscope image of the carbon fiber substrate used in Example 1 of the present invention, with a scale of 5 μm.
[0032] Figure 2 This is a scanning electron microscope image of the flexible humidity photoluminescent fiber prepared in Example 1 of the present invention, with scales of 50 μm and 2 μm respectively.
[0033] Figure 3 These are optical photographs of the flexible humidity photoluminescent fiber prepared in Example 1 of the present invention luminescing when wet (from left to right, the comparisons are water, DMF, ethanol, DMSO, and pure water blank).
[0034] Figure 4 This is a fluorescence spectrum of the organic metal framework in the flexible humidity photoluminescent fiber prepared in Example 1 of the present invention.
[0035] Figure 5 This is a comparison chart of the luminous intensity of the flexible humidity photoluminescent fiber prepared in Example 1 of the present invention at different humidity levels (the left side is a saturated solution of potassium carbonate with a relative humidity of 43.2%; the right side is a saturated solution of potassium sulfate with a relative humidity of 97.3%).
[0036] Figure 6 This is a scanning electron microscope image of the flexible humidity photoluminescent fiber prepared in Comparative Example 1 of the present invention, with a scale of 50 μm. DETAILED DESCRIPTION
[0037] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0038] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.
[0039] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.
[0040] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0041] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0042] In the description of the embodiments of the present application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).
[0043] In the description of the embodiments of the present application, the technical terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential", etc. indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, which are only for the convenience of describing the embodiments of the present application and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the embodiments of the present application.
[0044] In the description of the embodiments of the present application, unless otherwise clearly specified and limited, technical terms such as "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, and it can be the internal connection of two elements or the interaction relationship between two elements. For those of ordinary skill in the art, the specific meanings of the above terms in the embodiments of the present application can be understood according to the specific circumstances.
[0045] In order to solve the technical problem that it is extremely difficult to stably and firmly load fluorescent particles on the fiber surface, the present application provides a method for preparing a flexible humidity photoluminescent fiber, which directly uses a flexible high-temperature resistant fiber as a substrate, and hydrothermally grows regular rare earth metal organic framework small particles on its surface to obtain a flexible humidity photoluminescent fiber. When the fiber material is wet, it can emit bright blue light under ultraviolet light, that is, the humidity photoluminescent fiber is obtained. Specifically, the following steps are included:
[0046] S1, first, using N,N-dimethylformamide as a solvent to prepare a 2-aminoterephthalic acid solution; then, adding a rare earth metal organic framework precursor to obtain a precursor mixed solution;
[0047] S2, performing ultrasonic treatment on the precursor mixed solution;
[0048] S3, placing the pretreated high temperature resistant fiber in the ultrasonically treated precursor mixed solution for hydrothermal reaction, wherein the hydrothermal temperature is 120 to 180° C. and the reaction time is 24 to 72 hours;
[0049] S4, after the hydrothermal reaction is completed and the solution is cooled to room temperature, the high temperature resistant fiber is taken out and cleaned and dried, and humidity-sensitive photoluminescent organic metal framework particles with a predetermined thickness, predetermined particle size and crystal form are uniformly deposited on the surface of the flexible high temperature resistant fiber to obtain a flexible humidity photoluminescent fiber.
[0050] Preferably, in the precursor mixed solution in step S1, the concentration of the rare earth metal organic framework precursor is 0.02-0.06 mol / L; and the concentration of the 2-aminoterephthalic acid solution is 0.01-0.03 mol / L.
[0051] Preferably, in the precursor mixed solution in step S1, the molar mass ratio of the rare earth metal organic framework precursor to 2-aminoterephthalic acid is 2.2:1.1.
[0052] Preferably, the rare earth metal organic framework precursor is a mixture of one or more of neodymium nitrate hexahydrate, europium nitrate hexahydrate, terbium nitrate hexahydrate, and terbium nitrate hexahydrate.
[0053] Preferably, in step S3, the high temperature resistant fiber is one of carbon fiber, metal-based fiber, polyester fiber, polytetrafluoroethylene fiber, and polyimide fiber.
[0054] Preferably, in step S3, the specific process of the hydrothermal reaction is: placing the precursor mixed solution in a hydrothermal reactor, and then placing the pretreated high temperature resistant fiber, wherein the hydrothermal temperature is 120-150° C., and the reaction time is 24-48 hours.
[0055] Preferably, in step S2, the ultrasonic treatment process is as follows: placing the precursor mixed solution in an ice bath at 0-10°C, the ultrasonic time is 10-30 minutes, and the ultrasonic power is 200-500W.
[0056] Preferably, in step S3, the pretreatment process of the high temperature resistant fiber is: placing the high temperature resistant fiber in water and alcohol solution in turn for ultrasonic cleaning, and then taking it out and drying it for standby use.
[0057] The preparation method of the flexible humidity-induced photoluminescent fiber provided by the present invention is described below with reference to specific embodiments.
[0058] Example 1
[0059] Embodiment 1 of the present invention provides a method for preparing a flexible humidity-induced photoluminescent fiber, comprising the following steps:
[0060] S1. Add 0.2 mmol of 2-aminoterephthalic acid to 20 mL of N,N-dimethylformamide solvent to prepare a 0.01 mol / L 2-aminoterephthalic acid solution; then take 0.4 mmol of neodymium nitrate hexahydrate and add it to the 0.01 mol / L 2-aminoterephthalic acid solution to obtain a precursor mixed solution of neodymium nitrate hexahydrate, 2-aminoterephthalic acid and N,N-dimethylformamide;
[0061] S2, placing the precursor mixed solution of neodymium nitrate hexahydrate, 2-aminoterephthalic acid and N,N-dimethylformamide described in step S1 in a cell crusher, and ultrasonicating it at a power of 300 W for 30 minutes in an ice bath at 2°C for use;
[0062] S3, placing the carbon fiber (with an average fiber diameter of about 5 μm) in deionized water and ethanol for ultrasonic cleaning for 15 minutes, drying and storing for later use; transferring the precursor mixed solution containing neodymium nitrate hexahydrate, 2-aminoterephthalic acid and N,N-dimethylformamide treated by ultrasound in step S2 to a 100 mL polytetrafluoroethylene liner, and then placing the cleaned carbon fiber into the aforementioned precursor mixed solution, and hydrothermally reacting at 120° C. for 48 hours;
[0063] In the mixed solution system, the following reaction process can occur when neodymium nitrate hexahydrate, 2-aminoterephthalic acid and N,N-dimethylformamide are mixed: MOF first grows uniformly on the fiber surface in a thin line under hydrothermal conditions, and the binding force between the MOF and the fiber interface increases. After a dense film is formed, the interaction between the MOFs causes the thin line MOF to further combine into a spherical shape to increase the deposition amount of MOF. After two morphological changes of MOF, the present invention can directly realize the stable and uniform deposition load of fluorescent organic metal framework particles on the smooth fiber surface;
[0064] S4. After the hydrothermal reaction is completed and the solution is cooled to room temperature, the composite fiber is taken out, cleaned with DMF and ethanol in turn, and dried to obtain a flexible humidity photoluminescent fiber; and the precipitate is collected for later use.
[0065] See also Figure 1 to Figure 2 As shown, from Figure 1 It can be seen that when the carbon fiber substrate is not treated, the fiber surface is a smooth structure. Figure 2 It can be seen that after the hydrothermal reaction, a thick layer of Nd-MOF spherical particles with a diameter of about 1 to 2 μm is densely grown and deposited on the surface of the carbon fiber.
[0066] Among them, the crystal form of the Nd-MOF spherical particles is a monoclinic system (in which each europium ion adopts a nine-coordination mode to form a 2D network structure, which will promote the loading amount of MOF on the fiber, and the loading effect of this crystal form is significantly better than other conventional crystal forms), and the deposition thickness is 3μm.
[0067] The flexibility and mechanical properties of the flexible humidity photoluminescent fiber prepared in Example 1 are relatively good, wherein the mechanical properties are better than the original mechanical properties of pure carbon fiber.
[0068] See also Figure 3 As shown, the humidity photoluminescent fiber prepared in Example 1 of the present invention will emit bright blue fluorescence only when it comes into contact with water.
[0069] See also Figure 4 As shown, the humidity photoluminescent fiber prepared in Example 1 of the present invention has a maximum fluorescence intensity in the visible light band when the excitation wavelength is in the range of 320 to 360 nm.
[0070] Please refer to Figure 5 As shown, with the change of humidity, the prepared photoluminescent fiber emits blue fluorescence of different brightness. When the humidity is low, the blue fluorescence emitted by the fiber is weaker, and when the humidity is high, the fiber emits stronger blue fluorescence.
[0071] Comparative Example 1
[0072] Comparative Example 1 provides a method for preparing a flexible humidity-induced photoluminescent fiber. Compared with Example 1, the difference is that in step S1, the carbon fiber is not surface pretreated, and the rest is substantially the same as Example 1 and will not be repeated here.
[0073] See also Figure 6 As shown, the MOF particles deposited on the fiber surface prepared in Comparative Example 1 are less, which is mainly due to the presence of impurities on the surface of the unpretreated carbon fiber, resulting in a reduction in the deposition loading of the rare earth metal organic framework particles.
[0074] Comparative Example 2
[0075] Comparative Example 1 provides a method for preparing a flexible humidity photoluminescent fiber. Compared with Example 1, the difference is that in step S1, the solvent of 2-aminoterephthalic acid (N,N-dimethylformamide) is replaced by deionized water, and the rest is basically the same as Example 1 and will not be repeated here.
[0076] There are no particles on the surface of the fiber prepared in Comparative Example 2. This is mainly because the water solvent will affect the synthesis of the rare earth metal organic framework particles. Specifically, the MOF particles prepared in Example 1 of the present invention will dissolve when encountering water, so MOF particles cannot be synthesized using water as a solvent. However, the N,N-dimethylformamide in Example 1 can enable the rare earth metal organic framework particles to achieve stable and firm deposition loading.
[0077] Comparative Example 3
[0078] Comparative Example 1 provides a method for preparing a flexible humidity-induced photoluminescent fiber. Compared with Example 1, the difference is that in step S2, the precursor mixed solution is not subjected to ultrasonic treatment. The rest is substantially the same as Example 1 and will not be repeated here.
[0079] The MOF particles deposited on the fiber surface prepared in Comparative Example 3 are uneven, which is mainly due to the uneven mixing of the precursor mixed solution that has not been ultrasonically treated; the present application adopts low-temperature ultrasonic treatment, which can achieve the technical effect of uniformly dispersing the precursor solution, thereby significantly increasing the deposition loading capacity of rare earth metal organic framework particles.
[0080] Embodiment 2-5
[0081] This embodiment 2-5 provides a method for preparing a flexible humidity photoluminescent fiber. Compared with embodiment 1, the difference is that in step S1, the fiber substrate is replaced with metal-based fiber, polyester fiber, polytetrafluoroethylene fiber, polyimide fiber, and the rest is basically the same as embodiment 1 and will not be repeated here.
[0082] Table 1 shows the performance parameters of Examples 1 to 5.
[0083] Example High temperature resistant fiber types Fluorescence performance Deposition thickness Particle size Granular crystal form Example 1 Carbon Fiber good 2~4μm 1~2μm Monoclinic system Example 2 Metal-based fibers good 2~4μm 1~2μm Monoclinic system Example 3 Polyester good 2~4μm 1~2μm Monoclinic system Example 4 Polytetrafluoroethylene fiber good 2~4μm 1~2μm Monoclinic system Example 5 Polyimide fiber good 2~4μm 1~2μm Monoclinic system
[0084] It can be seen from Table 1 that the influence of fiber types on humidity-sensitive photoluminescence and mechanical properties is that different fiber types do not affect the deposition thickness, particle size and crystal form of MOF particles, and have no effect on the humidity-sensitive photoluminescence and mechanical properties of the fibers.
[0085] Embodiment 6-10
[0086] The present embodiments 6-10 provide a method for preparing a flexible humidity photoluminescent fiber. Compared with embodiment 1, the difference is that in step S1, the molar mass ratio of the rare earth metal organic framework precursor and 2-aminoterephthalic acid is set differently, and the rest is roughly the same as embodiment 1 and will not be repeated here.
[0087] Table 2 shows the performance parameters of Example 1, Examples 6-10
[0088]
[0089] As can be seen from Table 2, the effect of the molar mass ratio of rare earth metal organic framework precursor and 2-aminoterephthalic acid on the humidity-sensitive photoluminescence performance and mechanical properties is: more or less rare earth metal organic framework precursor will lead to a decrease in MOF deposition thickness and particle size, thereby causing a decrease in luminescence performance, but will not affect the crystal form of the particles and the mechanical properties of the fiber.
[0090] Among them, the effect of deposition thickness on fiber performance is: the thicker the deposited MOF particles, the longer the fiber's luminescence time and the less likely it is to be quenched; too thick a deposition will cause the MOFs particles to be loosely bound to the fiber, resulting in detachment and reduced fiber luminescence performance. The effect of deposition thickness on fiber mechanical properties is: when the deposition thickness is within an appropriate range, the fiber's mechanical properties will be improved to a certain extent, and when the deposition thickness exceeds a certain range, the fiber's mechanical properties will be reduced.
[0091] The effect of particle size on fiber performance is: if the particle size is too large, the adhesion of the particle on the fiber surface will be smaller, and the fiber luminescence performance will be worse. The effect of particle size on fiber mechanical properties is: the size of particle size does not affect the mechanical properties of the fiber.
[0092] The influence of particle crystal form on fiber performance is: the particle crystal form is regular, and the fiber luminescence performance is better. The influence of particle crystal form on fiber mechanical properties is: particle crystal form does not affect the mechanical properties of the fiber.
[0093] Examples 11-14
[0094] The present embodiments 11-14 provide a method for preparing a flexible humidity photoluminescent fiber. Compared with embodiment 1, the difference is that in step S1, the type of rare earth metal organic framework precursor is different. The rest is substantially the same as embodiment 1 and will not be described again.
[0095] Table 3 shows the performance parameters of Example 1 and Examples 11-14
[0096]
[0097] It can be seen from Table 3 that the influence of the type of rare earth metal organic framework precursor on the humidity-sensitive photoluminescence performance and mechanical properties is: different rare earth metal organic framework precursors do not affect the deposition thickness and particle size of MOF particles, and have no effect on the humidity-sensitive photoluminescence performance and mechanical properties of the fiber.
[0098] Examples 15-23
[0099] The present embodiments 15-23 provide a method for preparing a flexible humidity photoluminescent fiber. Compared with embodiment 1, the difference is that in step S3, the hydrothermal reaction temperature and the hydrothermal reaction time are set differently. The rest is roughly the same as embodiment 1 and will not be repeated here.
[0100] Table 4 shows the performance parameters of Example 1 and Examples 15-23
[0101]
[0102]
[0103] As can be seen from Table 4, the effects of hydrothermal reaction temperature and hydrothermal reaction time on humidity-sensitive photoluminescence properties and mechanical properties are: too high a hydrothermal reaction temperature or too long a hydrothermal reaction time will lead to excessive MOF particle deposition thickness and particle size, decreased particle adhesion, and decreased fiber fluorescence properties; too low a hydrothermal reaction temperature or too short a hydrothermal reaction time will lead to unformed MOF particles or fewer synthesized particles, thereby affecting the luminescence properties; but this will not affect the crystal form of the particles and the mechanical properties of the fiber.
[0104] Examples 24-28
[0105] Embodiments 24-28 provide a method for preparing flexible humidity-induced photoluminescent fibers. Compared with Embodiment 1, the difference is that in step S2, the ultrasonic parameters are set differently. The rest is roughly the same as Embodiment 1 and will not be repeated here.
[0106] Table 5 shows the performance parameters of Example 1 and Examples 24-28
[0107]
[0108] It can be seen from Table 5 that the effects of ultrasonic parameters on the humidity-sensitive photoluminescence properties and mechanical properties are as follows: within a reasonable range, the ultrasonic parameters have no effect on the synthesis of MOF particles and their deposition on the fiber surface, thereby not affecting the humidity-sensitive photoluminescence properties and mechanical properties of the fiber.
[0109] In summary, the present invention provides a flexible humidity photoluminescent fiber and a preparation method and application thereof, which relates to the technical field of photoluminescent fiber preparation. The preparation method directly uses a flexible high-temperature resistant fiber as a substrate, and hydrothermally grows regular rare earth metal organic framework small particles on its surface to obtain a flexible humidity photoluminescent fiber. When the fiber material is wet, it can emit bright blue light under ultraviolet light, thus obtaining a humidity photoluminescent fiber. Specifically, the method includes the following steps: S1, first, using N,N-dimethylformamide as solvent to prepare 2-aminoterephthalic acid solution; then, adding rare earth metal organic framework precursor to obtain a precursor mixed solution; S2, ultrasonically treating the precursor mixed solution; S3, placing the pretreated fiber in the ultrasonically treated precursor mixed solution for hydrothermal reaction, wherein the hydrothermal temperature is 120-180°C and the reaction time is 24-72h; S4, after the hydrothermal reaction is completed and the solution is cooled to room temperature, the fiber is taken out and washed and dried for post-processing, and humidity-sensitive photoluminescent organic metal framework particles with a predetermined thickness, predetermined particle size and crystal form are uniformly deposited on the surface of the flexible fiber to obtain a flexible humidity photoluminescent fiber. The obtained flexible humidity photoluminescent fiber has good flexibility, fast response time, excellent stability and brightness of luminescence, and has good application prospects in the fields of smart wearables and visualized smart fibers.
[0110] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A method for preparing a flexible humidity photoluminescent fiber, characterized in that: The steps include: S1, first, using N,N-dimethylformamide as a solvent to prepare a 2-aminoterephthalic acid solution; then, adding a rare earth metal organic framework precursor to obtain a precursor mixed solution; S2, performing ultrasonic treatment on the precursor mixed solution; S3, placing the pretreated high temperature resistant fiber in the ultrasonically treated precursor mixed solution for hydrothermal reaction, wherein the hydrothermal temperature is 120 to 180° C. and the reaction time is 24 to 72 hours; S4, after the hydrothermal reaction is completed and the solution is cooled to room temperature, the fiber is taken out and cleaned and dried for post-processing, and humidity-sensitive photoluminescent organic metal framework particles with a predetermined thickness, predetermined particle size and crystal form are uniformly deposited on the surface of the flexible high-temperature resistant fiber, thereby obtaining a flexible humidity-sensitive photoluminescent fiber.
2. The method for preparing the flexible humidity photoluminescent fiber according to claim 1, characterized in that: In the precursor mixed solution of step S1, the concentration of the rare earth metal organic framework precursor is 0.02-0.06 mol / L; the concentration of the 2-aminoterephthalic acid solution is 0.01-0.03 mol / L.
3. The method for preparing the flexible humidity photoluminescent fiber according to claim 2, characterized in that: In the precursor mixed solution of step S1, the molar mass ratio of the rare earth metal organic framework precursor to 2-aminoterephthalic acid is 2:
1.
4. The method for preparing the flexible humidity photoluminescent fiber according to claim 1, characterized in that: The rare earth metal organic framework precursor is a mixture of one or more of neodymium nitrate hexahydrate, europium nitrate hexahydrate, terbium nitrate hexahydrate, and terbium nitrate hexahydrate.
5. The method for preparing the flexible humidity photoluminescent fiber according to claim 1, characterized in that: In step S3, the high temperature resistant fiber includes but is not limited to one of carbon fiber, metal-based fiber, polyester fiber, polytetrafluoroethylene fiber, and polyimide fiber; The pretreatment process of the high temperature resistant fiber is: placing the high temperature resistant fiber in water and alcohol solution in turn for ultrasonic cleaning respectively, and then taking it out for drying and standby use.
6. The method for preparing the flexible humidity photoluminescent fiber according to claim 1, characterized in that: In step S3, the specific process of the hydrothermal reaction is: placing the precursor mixed solution in a hydrothermal reaction kettle, and then placing the pretreated fiber, wherein the hydrothermal temperature is 120-150° C., and the reaction time is 24-48 hours.
7. The method for preparing the flexible humidity photoluminescent fiber according to claim 1, characterized in that: In step S2, the ultrasonic treatment process is as follows: placing the precursor mixed solution in an ice bath at 0-10°C, the ultrasonic time is 10-30 minutes, and the ultrasonic power is 200-500W.
8. The method for preparing the flexible humidity photoluminescent fiber according to claim 1, characterized in that: In step S3, the particle size of the humidity-sensitive photoluminescent organic metal framework particles is 1-2 μm, the crystal form is monoclinic system, and the deposition thickness is 2-4 μm.
9. A flexible humidity photoluminescent fiber, characterized in that: The fiber is prepared by the method for preparing the flexible humidity photoluminescent fiber according to any one of claims 1 to 8; The flexible humidity photoluminescent fiber comprises a high temperature resistant fiber matrix and humidity sensitive photoluminescent organic metal framework particles uniformly deposited and loaded on the surface of the high temperature resistant fiber; the humidity sensitive photoluminescent organic metal framework particles have a particle size of 0.5 to 2.5 μm, a monoclinic crystal form, and a deposition thickness of 1 to 4 μm; The flexible humidity photoluminescent fiber is stimulated by the change of environmental humidity and emits blue fluorescence under the irradiation of ultraviolet light.
10. The flexible humidity photoluminescent fiber according to claim 9, or the use of the flexible humidity photoluminescent fiber prepared by the method for preparing the flexible humidity photoluminescent fiber according to any one of claims 1 to 8, characterized in that: The flexible humidity photoluminescent fiber is applied in the fields of smart wearables, smart anti-counterfeiting and environmental monitoring.
Citation Information
Patent Citations
Fluorescence organic framework based on electrostatic spinning technology and preparation method thereof
CN107747222A
Metal organic framework / carbon nanofiber composite membrane material and preparation method thereof
CN107201645A
Preparation method and application of carbon fiber-based nano composite material
CN113684679A
Ultraviolet-resistant water-guiding fiber
CN118653304A